Primary Pulmonary Anaplastic Large Cell Lymphoma: A Rare Malignancy and Rare Cause of the Luftsichel Sign - Elizabeth Von Ende; Travis Kauffman; Philip A. Munoz; Santiago Martinez-Jiménez (Case Reports in Radiology)
Primary pulmonary lymphomas are rare with primary pulmonary non-Hodgkin lymphoma accounting for only 0.3% of primary lung neoplasms. Of these, the large majority are made up of marginal zone B-cell lymphoma and diffuse large B-cell lymphoma. We present a case of a very rare primary pulmonary anaplastic large cell lymphoma presenting as the luftsichel sign on chest radiograph. Pertinent imaging and pathology findings are discussed.